2016
DOI: 10.1002/ejlt.201500589
|View full text |Cite
|
Sign up to set email alerts
|

Production of concentrates of CLA obtained from sunflower and safflower and their application to the lipase‐catalyzed acidolysis of egg yolk phosphatidylcholine

Abstract: The process of acidolysis of egg yolk phosphatidylcholine (PC) with concentrates of conjugated linoleic acid (CLA) was performed. CLA was obtained by the alkali isomerization of sunflower and safflower oils. Analysis of the influence of different reaction conditions on the process of isomerization was investigated. Reactions were carried out in preparative scale at 150°C in the ethylene glycol and afforded the mixture of isomers: cis-9,trans-11 and trans-10,cis-12. Their content was 30.8 and 32.3% for product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The temperature of the reaction mixture in our study was 150 °C, equal to the boiling point of mixture. Some researchers conducted a study on the effect of different temperatures (150, 170, 180, and 200 °C) of conventional heating on production of CLA from LNA by direct alkali isomerization of sunflower and safflower oils (Niezgoda et al, ). They reported that the isomerization degree was about 40% for 12 h at 150 °C and was 100% after 2 h at 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the reaction mixture in our study was 150 °C, equal to the boiling point of mixture. Some researchers conducted a study on the effect of different temperatures (150, 170, 180, and 200 °C) of conventional heating on production of CLA from LNA by direct alkali isomerization of sunflower and safflower oils (Niezgoda et al, ). They reported that the isomerization degree was about 40% for 12 h at 150 °C and was 100% after 2 h at 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These biocatalysts were selected based on the literature data indicating that mentioned lipases effectively catalyze the structural modifications of natural triacylglycerols and natural or synthetic phospholipids [ 27 , 28 , 29 ]. Reaction conditions were also established after the analysis of literature data, suggesting that in order to enrich the PC with natural compounds other than fatty acids, it is necessary to use much higher molar excess of acyl donors and toluene as the reaction medium [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our research group, we elaborated the lipase-catalyzed incorporation of different biologically active acids ( n -3 PUFA, n -6 PUFA, or conjugated fatty acids) into PC using natural plant oils as the acyl donors i.e., sunflower oil, linseed oil, pomegranate seed oil [ 31 , 32 ]. The concentrates of CLA obtained from sunflower and safflower oil were also used to produce CLA-enriched PLs [ 33 ].…”
Section: Introductionmentioning
confidence: 99%